Nomadic Ethics: Attending to the Ghosts we Cite - Carter, Stephen P. (Art/Research International, 2022)
In response to Maureen Flint’s (2020) performance and essay, Fingerprints and Pulp, on the ethics of truncating and flattening research participants in qualitative research, I extend this ethical concern to the voices of scholars flattened in qualitative research and writing processes. Scholars cite for many reasons, but what is there that holds us to account for our treatments of academics that come before; how can we avoid flattening and abusing those we cite? Through endeavouring to recognise and protect ghosts and nomadic identities of those other than the author in the research and writing process, I propose a new way of re-animating and re-embodying the haunting, nomadic voices in cited texts, in order to minimise further, future truncations and limitations of the other in academic writing. Attending to the ghosts allows for more ethical and just behaviour towards those cited. Seeing the multitude of ghosts haunting scholarly work obliges more ethical behaviour toward those voices flattened in writing.